Vodní měkkýši Vysočiny - Luboš Beran (Malacologica Bohemoslovaca, 2017)
This paper summarizes data about the distribution of freshwater molluscs in the Vysočina Region (6,800 km2). The region is one of the 14 regions of the Czech Republic, situated in its central part. The major part of this region consists of Českomoravská vrchovina (Bohemian-Moravian Highlands) with average elevation about 500 m a. s. l. Data about freshwater molluscs have been obtained by author’s field research since 1993 and from many published and unpublished papers, private collections, and collections in museums dating from 1850. Altogether, data about the occurrence of 49 species of freshwater molluscs (27 gastropods, 22 bivalves) were obtained. This number constitutes 62% of all aquatic mollusc species found in the Czech Republic. Data about the occurrence of individual species were used for the construction of distributional maps of records for three time periods (1851–1950, 1951–2000, 2001–2016). The major part of the data has originated for the last period. This clearly demonstrates a significant increase in the research intensity after 2000. The most common species, i.e. recorded at least in 40 mapping cells out of 72 covering the area to the Vysočina Region, were Galba truncatula, Radix auricularia, R. labiata, Lymnaea stagnalis, Gyraulus albus, Ancylus fluviatilis, Anodonta anatina, Pisidium casertanum, and P. subtruncatum. In contrast, Viviparus viviparus, Potamopyrgus antipodarum, Stagnicola corvus, Radix ampla, R. balthica, Planorbis planorbis, Gyraulus acronicus, Ferrissia fragilis, Unio tumidus, Pseudanodonta complanata, Sinanodonta woodiana, Pisidium amnicum, P. tenuilineatum, and Dreissena polymorpha have been found in less than five mapping cells and belong to rare species of this region. Except 29 common and widespread species, four species (Bythinella austriaca, Physa fontinalis, Pisidium milium, and P. supinum) belonging in the Red List of the Molluscs of the Czech Republic were recorded. Other six species are classified as Vulnerable (Radix ampla, Gyraulus acronicus, Segmentina nitida, Unio tumidus, Anodonta cygnea, and Pisidium hibernicum), three as Endangered (Unio crassus, Pseudanodonta complanata, and Pisidium amnicum), and two as Critically Endangered (Margaritifera margaritifera and Pisidium tenuilineatum).